Associations Between Childhood Sexual Abuse, Intimate Partner Violence Trauma Exposure, Mental Health, and Social Gender Affirmation Among Black Transgender Women (Mary Ann Liebert, 2023)
Introduction: The purpose of this study was to examine associations between social gender affirmation and mental health outcomes. The resulting relationships were explored within the context of childhood sexual abuse (CSA) and intimate partner violence (IPV) trauma history. Materials and Methods: A community sample of 138 Black trans women completed structured interviews assessing gender affirmation, mental health, and trauma history. Bivariate associations between gender affirmation scale and mental health measures were assessed using Pearson coefficients. Multiple linear regression models were used to generate adjusted estimates of association. Results: Childhood sexual victimization and IPV were common. Depressive symptoms, anxiety, quality of life, and body image satisfaction were significantly associated with social gender affirmation. Recent IPV dampened this association to not significant. Gender affirmation and anxiety/panic and quality-of-life outcomes did not retain significance in models adjusted for lifetime IPV. CSA did not weaken the association. Conclusion: Incorporating trauma-informed and gender-affirmative frameworks into medical care and evidence-based interventions is a crucial structural step toward protection of the mental health of Black trans women.